Seroprevalence of Toxocara infection among healthy individuals referred to the medical center laboratories in Tehran City, Capital of Iran - Zahra Baghani; Hooshang Khazan; Mohammad Reza Sohrabi; Ali Rostami (Novelty in Biomedicine, 2018)
Background: Toxocarosis is a zoonotic disease with worldwide distribution. Humans’ infection occurred by incidental ingestion of eggs shed in feces of dogs or cats. Studies on general population are rare in Iran. In this cross-sectional study, we investigated seroprevalence, and risk factors associated with toxocariasis among the healthy individuals in Tehran, capital if Iran. Materials and Methods: In total, 374 sera samples were investigated for the presence of anti-Toxocara IgG. We applied ELISA as screening test using available commercial kit. In addition, demographic data were obtained from participant’s questionnaires. Data analysis was performed using SPSS16. Results: The overall seroprevalence of toxocariasis was found 5.6% (21/374). Regarding the socio-demographic variables, age (P<0.001) and eating unwashed vegetables (P=0.049) were significantly associated to toxocariasis in univariate analysis. In the logistic regression analysis, only age (P<0.001) was identified as potential risk factor associated with Toxocara infection. Conclusion: This study revealed that seroprevalence of toxocariasis is relatively low in the healthy individuals in Tehran. We suggest carrying out further studies in the different part of Iran and investigate on the prevalence of toxocariasis in high-risk groups such as asthma, hyper-eosinophilic, epilepsy, rheumatism and schizophrenia patients.